Pengaruh Penerapan Akuntansi Pertanggungjawaban dan Sistem Akuntansi Manajemen Terhadap Pengendalian Biaya Pada BPR Tanaoba Lais Manekat Kupang - Ayu Dafriana Windra Pia; Markus A.K.B Hallan; Eve Ida Malau (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2025)
This study aims to examine the effect of responsibility accounting implementation and management accounting systems on cost control at BPR Tanaoba Lais Manekat Kupang. Data were collected through questionnaires from 126 respondents using a saturated sampling technique. A quantitative method was employed, including tests of validity, reliability, classical assumptions (normality, multicollinearity, heteroscedasticity), multiple linear regression analysis, and hypothesis testing (t-test, F-test, determination coefficient). The results indicate that both responsibility accounting and management accounting systems have a significant partial and simultaneous impact on cost control. This study provides empirical evidence contributing to improving cost efficiency in the microfinance banking sector.